The anti-androgen drug dutasteride renders triple negative breast cancer cells more sensitive to chemotherapy via inhibition of HIF-1α-/VEGF-signaling. (30th October 2014) - von Wahlde, Marie-Kristin; Hülsewig, Carolin; Ruckert, Christian; Götte, Martin; Kiesel, Ludwig; Bernemann, Christof
Abstract: Background : Triple negative breast cancer (TNBC) is characterized by lack of expression of both estrogen and progesterone receptor as well as lack of amplification of HER2. Patients with TNBC carry an unfavorable prognosis compared to other breast cancer subtypes given that endocrine or HER2 targeted therapies are not effective, rendering chemotherapy the sole effective treatment option to date. Therefore, there is a high demand for additional novel treatment options. Findings : We previously published a list of genes showing both higher gene expression rates in TNBC and, in addition, are known to encode targets of non-oncologic drugs. SRD5A1, which encodes the type-1 isoform of the steroid-5alpha-reductase, which is involved in androgen metabolism, was found to be one of these genes. Dutasteride is a dual blocker of both the type-1 and type-2 isoform of SRD5A1 and is indicated in the treatment of benign prostate hyperplasia. Treatment of TNBC cell lines with dutasteride was associated with a dose-dependent decrease in cell viability, altered protein expression of VEGF and HIF-1α and increased chemosensitivity. Conclusion : Our results demonstrate that the SRD5A1-corresponding anti-androgenic drug dutasteride might act as a combinatorial therapeutic option besides standard chemotherapy in highly aggressive TNBC.